A Study of Relationship between Organizational Culture and Social Responsibility among School Teachers – With Special Reference to Teachers in Kottayam District: Examining the Impact of Organizational Culture on the Social Responsibility of School Teachers in Kottayam District (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Organizational culture refers to the beliefs and behaviors that determine how a company's employees and management interact and handle outside business transactions. Social Responsibility is the way how an individual or organizations carry out their business or their day to day activity or their job or business which is ethical and how they handle their day to day practice to have positive impact on society. People are affected by the culture in which they live. Similarly, an individual working for any organization with a firmly established culture will be taught the values, beliefs, and expected behaviors of that organization. There is at least some sound evidence that variations in cultural values may have a significant impact on employee’s social responsibility and job performance.In keeping with this it is seen that the workplace behaviors, internal communication, discipline in the organization, workplace co-ordination, organization values and organization vision can increase social responsibility among school teachers. As far as the individual variable is concerned, it is predicted that organization vision, workplace co-ordination, organization value and discipline in the organization are the most influencing factors that have strong relationship with social responsibility.